"A Life Slips Through Our Fingers" Experiences of Nurses Working in Pediatric Intensive Care Units About Children's Death: A Qualitative Study - Ozsavran, Musa; Kurt, Aylin; Ayyildiz, Tulay Kuzlu; Gul, Zeynep; Kurt, Aylin (Sage Publications Inc, 2026)
Caring for a dying child can be an experience full of all kinds of negative emotions, pain and stress for the pediatric nurse. In this study, which was carried out in Turkey, we aimed to determine how nurses working in a pediatric intensive care unit remembered and made sense of their experiences regarding children's deaths. In-depth interviews were held with 13 nurses. The data were analyzed using the content analysis method. Three themes were identified. These were (1) Personal effects of death, (2) Difficulties in care, and (3) Coping with death. It was clear that the nurses were traumatised by their exposure to infant deaths. The findings showed that nurses experienced regret, fatigue and posttraumatic stress disorder. In addition, it was determined that nurses should be supported to cope with child deaths, which is a complicated process involving the child and the family, especially emotionally. Moreover, providing institutional support to nurses and referring them to cognitive-behavioral therapies may make it easier for them to cope with the emotional burden they carry, as well as the burnout they experience.
Keywords: Nursing; Children; Intensive Care Unit; Death; Difficulties In Care; Coping